The Literasi Keagamaan di Era Informasi: Tantangan dan Peran PAI dalam Menyaring Hoaks dan Misinformasi - Sundari, Siti; Hidayat, Wahyu; Rifky Septian, Rachmat; Hairiyanto (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
The digital information era has brought a new dimension to the dissemination of knowledge, including religious information. Social media and online platforms have become the main channels for individuals to access and share religious content, but both also provide opportunities for the spread of fake news and misinformation, which have the potential to cause social unrest and distort understanding of religious teachings. This study aims to analyze the challenges of religious literacy in the context of the rise of digital information, especially related to the spread of fake news and misinformation related to religion among junior high school students in Central Bengkulu. Furthermore, this study examines the strategic role of Islamic Religious Education (PAI) subjects in developing critical and responsible religious literacy skills among students in the information era. Through a literature review and content analysis approach, this study identifies important religious literacy competencies, such as the ability to verify sources of information, a comprehensive understanding of the context of religious teachings, and increased awareness of the potential for information manipulation. In addition, this study explores how the PAI curriculum and learning methods can be adapted to equip students with the skills to filter information, identify fake news and religious misinformation, and promote peaceful and constructive religious narratives in the digital space. The findings of this study indicate that most students are exposed to too much unverified information, are vulnerable to the spread of fake news and misinformation, have limited digital literacy and critical thinking skills, and may be influenced by filter bubbles. On the other hand, although Islamic Religious Education (PAI) has not achieved optimal results, it has been proven to play an important role in developing students' ability to filter fake news and misinformation.